Peran Penggunaan Platform Digital Pemerintah Kabupaten Rembang dalam Membangun Kepercayaan Publik - Wiwik Mugiyono; Sutono Sutono; Mulyanto Mulyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Digital transformation in government has encouraged local governments to improve public service quality and strengthen public trust through the utilization of digital platforms. The Rembang Regency Government utilizes various digital platforms including websites, mobile applications, and social media to enhance transparency, interaction, and public communication effectiveness. This study aims to analyze the role of government digital platforms in building public trust and identify supporting and inhibiting factors using SWOT, IFAS, and EFAS analysis. This research employs a descriptive qualitative method using interviews, observations, and documentation as data collection techniques. The results indicate that digital platforms play an important role in increasing transparency and public engagement. The main strengths lie in information openness and platform diversity, while the weaknesses include limited digital literacy and system integration. Opportunities arise from increasing digital adoption in society, while threats include digital divide and misinformation. The recommended strategies include strengthening platform integration, improving content quality, and enhancing digital literacy. Transparency and responsiveness are identified as key factors in building public trust through digital government platforms.